Monetary Economics : Theory, Policy, and Institutions - Anyanwu, J. C. (Onitsha, Nigeria : Hybrid Publishers, 1993)
The book highlights theories, policies and monetary issue related to financial institutions.
Includes bibliographical references and index.
osc 7/7/17
Loans
Keywords: Monetary policy; Money; Financial institutions; Nigeria